Timing and growing conditions of nitrogen topdressing influence the grain yield and protein content of four wheat cultivars - Silva,Raphael Rossi (2019)
ABSTRACT The application of an adequate rate and splitting of nitrogen is essential for wheat grain yield and protein content. The aim of this work was to adjust nitrogen management approaches regarding agronomic performance and protein content of wheat cultivars in various environments. Field experiments were conducted under no-tillage system on soybean mulch during the 2011 and 2012 growing seasons in Londrina and Pato Branco regions. The experimental design was a randomized block in split plot with four replicates. Four wheat cultivars (IPR Catuara TM, BRS Gaivota, Quartzo, CD 120) were tested with six nitrogen (N) management forms. Were evaluated: number of ears per unit area (NEA); plant height (PH); thousand-kernel weight (TKW); test weight (TW); grain yield (GY); and protein content (PC). The combined ANOVA (p ? 0.01) and Tukey’s test (p ? 0.01) were used. The interaction between cultivars and environments influence all yield components, GY and PC. The interaction management forms of N and environments affected the TKW, NEA, GY and PC. The results showed that in low-rainfall environments, nitrogen topdressing could be suppressed with no negative effects on GY or PC. Under ideal weather conditions, the GY of wheat cultivars was enhanced on application of 60 kg.ha–1 N of urea at the beginning of tillering as well 20 kg.ha–1 of N at booting. Matching the appropriate cultivars to the ideal growth environment is essential for achieving high GY values. The nitrogen forms on the topdressing do not influence the PC of cultivars in Pato Branco.